Digital technology utilization and library's role in religious literacy - Nafisah, Syifaun; Rohaya, Siti; Effendy, Nazrul (Jurnal Kajian Informasi dan Perpustakaan, 2024)
Pesantren is an Islamic education institution widely available in Indonesia. Various issues, such as intolerance to radicalism related to Pesantren, have emerged. Pesantren has made multiple efforts to stem this issue, one of which is through religious literacy activities. The image of Santri, who has low information literacy skills, is also allegedly one of the factors that prompted the emergence of these issues. This research aimed to explore the use of digital technology in religious literacy activities in Pesantren Thawalib Parabek in West Sumatra. This study also examined libraries' role in religious literacy activities in Pesantren. This study used qualitative research with a field study approach and used primary data from interviews, observation, and documentation. The secondary data was collected from Pesantren documents. This study conducted credibility, transferability, dependability, and confirmability tests using triangulation and audit techniques to ensure the validation of research data. Pesantren utilized digital technology products in religious literacy activities. These products included web-based applications, social media, and live-streaming media. This media aimed to promote, document, and disseminate activity information. The library has a vital role in literacy activities in Pesantren, namely as a place, mediator, facilitator, and contributor who provides the information sources needed for these activities. Pesantren faces internal obstacles in using digital technology due to limitation policies on the use of technology in the Pesantren environment. To overcome these obstacles, the government can collaborate with libraries to carry out religious literacy activities in Pesantren.